‘Kidulthood’: Ethnography, juvenile prison violence and the transition from ‘boys’ to ‘men’ - Gooch, Kate (Criminology & criminal justice, 2019)
The article explores how teenage boys (aged 15-18 years old) in an English young offender institution (YOI) engage in and construct prison violence. Focusing on the relationship between violence and the performance of adolescent prison masculinities, it presents three key findings. First, there are key differences between juvenile and adult prison violence (behaviour that is framed in terms of being a ‘real man’ or a ‘little boy’). Second, the performance of masculinity is complicated by the striking vulnerability of child prisoners and masks the real problems that all young people experience ‘handling jail’. Third, the performance of ‘manhood’ is an unfinished, negotiated and incomplete work where young people exist in a state of liminality and ‘kidulthood’, catapulted into premature adulthood but retaining aspects of their childhood sensibilities and needs. Thus, gendered performances are mediated and constructed in accordance to youth and adulthood.